PENINGKATAN KEMAMPUAN MENYIMAK MELALUI KEGIATAN MESATUA - Gusti Ayu Nanik Ardhiani; Ni Ketut Erna Muliastrini; Ni Kadek Depi Dumaini (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2023)
This research is aimed at exploring the listening skills processing activity of class I students in SDN 1 Selat and investigating to what extend the processing result of listening skills can be improved through mesatua activities. This study is a classroom action research using Kemmis and Mc. Taggart research model. This study was conducted in 2 cycles with 8 meetings in cycle 1 and 8 meetings in last cycle where every cycle consisted of the following steps: planning, action, observation and reflection. The sample of this study was 21 class I students comprissing of 12 male students and 9 female students. The instruments used in this study was observational sheet of students activities using masatua activities. The data in this study were quantitative and qualitative data. Quantitative data were analyzed by using descriptive statistic to compare the result from the first and second cycle. While qualitative data from field notes and interview were analyzed through the following steps: data reduction, data display and data verification. The results of this study depicts that there was the improvement of listening skills through mesatua activities, proven by the listening skills mean score in pre-intervention which was 48,64 % gained 16,17 % improvement to 64,81 % in cycle I and keep increasing the gain into 17,50 % and become 82,31 % in cycle II.